Effect of temperature on mycelial growth of Trichoderma, Sclerotinia minor and S. sclerotiorum, as well as on mycoparasitism - Domingues,Manuel Victor Pessoni Fernandes (2016)
ABSTRACT Environmental conditions are very important for the biological control of plant diseases. In a previous study, isolates of Trichoderma asperellum (IBLF 897, IBLF 904 and IBLF 914) and T. asperelloides (IBLF 908) were selected as antagonists of S. minor and S. sclerotiorum, causal agents of lettuce drop, one of the most relevant diseases affecting the lettuce crop. In this subsequent study, the mycelial growth of these isolates and pathogens, as well as the mycoparasitism of isolate IBLF 914, was evaluated at different temperatures. The mycelial growth of the isolates of T. asperellum and T. asperelloides, as well as of S. minor and S. sclerotiorum, was evaluated at temperatures ranging from 7 to 42oC. The parasitism of propagules of S. minor and S. sclerotiorum by the isolate IBLF 914, as well as the number of lettuce seedlings surviving drop, was evaluated at 12, 17, 22, 27 and 32oC, in gerboxes containing substrate. S. minor and S. sclerotiorum showed mycelial growth at temperatures ranging from 7 to 27°C, but no growth occurred at 32 °C, and both pathogens had greater mycelial growth at 22°C. The isolates of Trichoderma grew at temperatures ranging from 12 to 37°C, with maximum growth at 27°C. The isolate IBLF 914 had mycoparasitism and reduced the disease in lettuce seedlings at temperatures ranging from 22 to 32°C. Since lettuce drop occurs when mild temperatures and high humidity prevail and the antagonist was more effective at higher temperatures, it is recommended that Trichoderma is applied in lettuce fields in Brazil also during warmer months of the year to reduce the inoculum remaining in the soil before planting the winter crop, which is more affected by the disease.